Full Text - Paz, Consuelo J.; del Corro, Anicia (The Archive, 2025)
More than 80% of the Philippine languages are considered minor. What are the criteria to consider them as such? What is the nature of the studies that have been done on them? Are these languages considered at all in language planning for the nation? These are some of the questions that this volume intends to answer, and in so doing, focus attention on Philippine minor languages, an aspect in Philippine linguistics which Philippine linguists have often neglected. The articles are arranged from the general to the more specific in scope, geographically moving from the north to the southern part of the Philippines.